The maelstrom of online programs in Colombian teacher education - Pedro Pineda; Jorge Celis (Arizona State University, 2018)
The replacement of direct human interaction by the computer connected to the internet is one of the most radical reforms in the history of education. In the first part, we show chronologically how-unlike correspondence, radio and television-the internet is the only technology that has sought to replace human interaction in teacher education training in Colombia. By consulting databases, we describe the institutionalization of online programs in terms of a maelstrom with problems and tensions that occur while growing exponentially to represent 18.3% and 33.8% of the offer in higher education and educational sciences in Colombia. In a second part, we compared the experience of 1,206 teachers who study postgraduate teacher training programs in Bogotá in both online and face-to-face modes through a student survey and a writing test. The results indicate lower weighted performances in the theoretical content and work volume among those who study their programs in the online modality, as well as a lower but statistically non-significant mean in teachers enrolled in online programs. The history and problems encountered in the importation of curricular models entirely based on the internet warrants being studied empirically in the teacher training programs to determine their educational effects.